2020
DOI: 10.1002/jsc.2335
|View full text |Cite
|
Sign up to set email alerts
|

Banking service in Bangladesh: The impact of service marketing mix on purchase intention of university students

Abstract: Banking plays a vital role in the financial life of an industry, and the significance of banks can be realized from the fact that they are measured as to be the life-blood of the modern economy. The Banking industry is considered as the mirror of any country. Banks are especially crucial for developing economies like Bangladesh, which has 57 listed banks. Due to increased competition, banks are trying to grab a new and growing market segment like the students' segment. So, there is a gap to explore student's p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 44 publications
0
9
0
4
Order By: Relevance
“…To limit the entry of non-sample participant, an introductory paragraph briefing the objective of the study and ethical issues of participating was attached to the beginning of the survey form. Finally, the survey questionnaire was shared with different Facebook groups as well as sent to potential participants through Facebook messenger, which was also applied in the past study (Hossain et al, 2020). A total of 340 responses were collected from three countries, e.g., Bangladesh (n ¼ 129), India (n ¼ 122), and Pakistan (n ¼ 89).…”
Section: Participant and Proceduresmentioning
confidence: 99%
“…To limit the entry of non-sample participant, an introductory paragraph briefing the objective of the study and ethical issues of participating was attached to the beginning of the survey form. Finally, the survey questionnaire was shared with different Facebook groups as well as sent to potential participants through Facebook messenger, which was also applied in the past study (Hossain et al, 2020). A total of 340 responses were collected from three countries, e.g., Bangladesh (n ¼ 129), India (n ¼ 122), and Pakistan (n ¼ 89).…”
Section: Participant and Proceduresmentioning
confidence: 99%
“…Physical evidence is evaluated by a higher education institution's target markets, ranging from the teaching materials to the appearance of the buildings and lecture facilities (Ivy, 2006). Several previous studies have shown there is an effect of the marketing mix on image (Eneizan et al, 2018;Esmaili et al, 2017;Kim & Hyun, 2011) and buying decisions or choosing decisions (Hossain et al, 2020;Mahmoud, 2018;Mahmoud et al, 2017) either directly or indirectly. Thus, the hypothesis is made as follows.…”
Section: Marketing MIX In Higher Educationmentioning
confidence: 99%
“…Nesse sentido, o mix de marketing pode ser definido como um conjunto de atividades empresariais que busca à satisfação das necessidades e desejos de um ou vários mercados, por meio da oferta de produtos adquiridos em um processo de troca (KOTLER; AR-MSTRONG, 2010; GOLAHIT; MAHAJAN, 2019). Dessa forma, o ambiente em que se acontece a referida troca, corresponde ao serviço real entregue aos consumidores e quaisquer mercadorias tangíveis que viabilizem a interação e a troca entre os clientes e empresas (HOSSAIN et al, 2020). Para Kotler e Armstrong (2010), o mix de marketing possui características que compõe cada um dos 4P's conforme se apresenta no Quadro 1.…”
Section: De Marketing (4p's)unclassified
“…Para Kotler e Armstrong (2010), o mix de marketing possui características que compõe cada um dos 4P's conforme se apresenta no Quadro 1. Com isso, o produto se configura como algo que é ofertado ao mercado para troca, uso e apreciação, com o propósito de atender aos desejos ou necessidades do consumidor (KOTLER, 2000;HOSSAIN et al, 2020). Desse modo, o produto para Las Casas (2006) é considerado como a parte mais importante e essencial do mix de marketing, sendo que este é o foco de comercialização das empresas.…”
Section: De Marketing (4p's)unclassified
See 1 more Smart Citation